BANK RISKS IN THE SYSTEM ON COUNTERING THE LAUNDERING OF PROCEEDS AND FINANCING OF TERRORISM - K.O. Shayakhmetova; A.T. Uteubayeva; А.А. Kabiyev; B.Т. Nazhmidenov (Academic Journal of Physical and Chemical Sciences, 2019)
The paper investigates the problems of bank risks in the system of countering the money-laundering and financing of terrorism. It was revealed that the considered field of finance-bank sector is in close interconnection and functioning with financial monitoring issues. Therefore, it is important to state that the issue of countering the legalization (laundering) of proceeds and financing of terrorism holds a specific place not only in Kazakhstan, but in other countries of the world too; the analysis was conducted. As the combating with criminal proceeds legalization is the most important means of control over the organized crime including its most harmful forms such as drug business and terrorism, the adoption by Kazakhstan of the generally recognized principles and mechanisms on countering the legalization of criminal proceeds and financing of terrorism has not only legal, but social and political significance. The risks, and, consequently, the control degree can differ significantly, the financial monitoring performers should possess the abilities to identify and verify the potentially suspicious transactions. The suggested methods and mechanisms to solve this problem will have beneficial effect on the work of the banking sector and economy of RK in whole.